2021
DOI: 10.3390/ma14071798
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Carbonation Profile with Raman Spectroscopy: Effects of Fly Ash and Ground Granulated Blast Furnace Slag

Abstract: Establishing a carbonation profile is of great significance to the prediction of the service life of reinforced concrete structures. In our previous work, Raman spectroscopy was shown to be an efficient tool for characterizing calcium carbonate (CaCO3) polymorphs and their profile in plain Portland cement (PC) matrices. However, as supplementary cementitious materials (SCMs), particularly fly ash (FA) and ground granulated blast furnace slag (GGBS), are widely used in concrete, establishing the carbonation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A further increase in temperature causes another loss of SS-FA mass at 750 °C. This phenomenon may be a consequence of the degradation of the grain wall surfaces caused by the release of gaseous products (CO 2 ) from their interior according to reaction Equation (7) [ 35 , 38 , 39 ]. Based on the literature, the presence of such CaCO 3 polymorphs as aragonite, vaterite, and calcite can be assumed [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…A further increase in temperature causes another loss of SS-FA mass at 750 °C. This phenomenon may be a consequence of the degradation of the grain wall surfaces caused by the release of gaseous products (CO 2 ) from their interior according to reaction Equation (7) [ 35 , 38 , 39 ]. Based on the literature, the presence of such CaCO 3 polymorphs as aragonite, vaterite, and calcite can be assumed [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, researchers [28,29] showed that GGBFS has outstanding workability and is resistant to chemical penetration by acids and seawater. Another study [30] provides a method for forecasting concrete durability using GGBFS. Moreover, previous studies [31,32] reported that using GGBFS as a cement replacement has a significant environmental impact because the CO2 emissions associated with cement production can be reduced and the cost of concrete production can be saved.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Song and Saraswathy (2006) [ 12 ], Caijun and Yinyu (1989) [ 13 ], Gruskovnjak et al, (2008) [ 14 ], Taylor (1997) [ 15 ], Shi et al, (2020) [ 16 ] and Duży et al, (2021) [ 17 ] showed that ground granulated blast furnace slag is known to have excellent workability and high resistance to chemical penetration by acids, seawater and sewage. And Yue et al, (2021) [ 18 ] suggest a method for predicting the durability of concrete using ground granulated blast furnace slag. In particular, Özbay et al, (2016) [ 19 ] and Kim et al, (2014) [ 20 ] reported that the utilization of ground granulated blast furnace slag as a cement replacement has a very significant impact on the environment, because the carbon dioxide emission involved in cement production can be reduced and the cost of concrete production can be saved.…”
Section: Introductionmentioning
confidence: 99%